ANALISIS FAKTOR FAKTOR YANG MEMPENGARUHI TINGKAT PENGUNGKAPAN INTERNET CORPORATE REPORTING - Fikrisani, Muchammad; Cahyonowati, Nur (Diponegoro Journal of Accounting, 2015)
The purpose of this study is to examine the factors that influence the level of internet corporate reporting disclosure on manufacturing companies listed on Bursa Efek Indonesia (BEI) in 2013. Variables used in this study are company size, public ownership, company performance, audit size, leverage and additional funds.The method of this study is secondary data analysis towards annual reports of manufacturing companies published in Bursa Efek Indonesia (BEI) in 2013. This study used purposive sampling method and multiple linear regression model as the analysis instrument. Before conducting the regression test, it was examined by the classical assumption tests.The result of this study indicates that public ownership, audit size and leverage do not have significant influence with the level of internet corporate reporting disclosure of a company. This study indicates that company size, company performance and additional fund have a significant influence with the level of internet corporate reporting disclosure of a company.